Infection with the delta agent in children. Issue 1 (January 1985) - Farci, P; Barbera, C; Navone, C; Bortolotti, F; Vajro, P; Caporaso, N; Vegnente, A; Ansaldi, N; Rizzetto, M; Tolentino, P
Abstract : Serological evidence of infection with the hepatitis B virus associated delta agent (delta) was found in 34 of 270 Italian children with HBsAg-positive liver disease. In different histological forms of chronic HBsAg hepatitis the prevalence of delta infection increased in parallel with the activity of the disease and was maximal in children with cirrhosis. During two to seven years of follow up the hepatitis deteriorated in 38% of the 34 patients with delta infection and ameliorated only in 9%. By contrast the disease usually ran a mild course in the 236 delta-negative carriers of HBsAg, with remission in 55% of these children and deterioration in only 7%. The outcome of chronic hepatitis associated with delta infection was not influenced by treatment with steroids and azathioprine. Chronic delta infection in children is usually accompanied by serious liver disease, that has a tendency to progress and is unresponsive to conventional immunosuppressive treatment.